Expand (2x + 5)(9x - 2).


Use the FOIL method:F - FIRST: the first term in either bracket, multiply: 2x(9x) = 18x2. O - OUTSIDE: the terms further from the centre of the brackets, multiply: 2x(-2) = -4x. I - INSIDE: the terms closer to the centre of the brackets, multiply: 5(9x) = 45x. L - LAST: the latter terms in either bracket, multiply: 5(-2) = -10. Now add the expressions from the four parts: 18x2 - 4x + 45x - 10 = 18x2 + 41x - 10.

Looking for more help? Search our library of answers.👇

Need help with Maths?
Boost your grades with stress-free tuition that fits your schedule.

About the author

Aaron H. is an online Maths tutor with MyTutor studying at Queen's, Belfast University